2015
DOI: 10.3390/ijms161226144
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Neuroprotective Factor Npas4 in Cerebral Ischemia

Abstract: Stroke is one of the leading causes of death and adult disability in the world. Although many molecules have been documented to have a neuroprotective effect, the majority of these molecules failed to improve the neurological outcomes for patients with brain ischemia. It has been proposed that neuroprotection alone may, in fact, not be adequate for improving the prognosis of ischemic stroke. Neuroprotectants that can regulate other processes which occur in the brain during ischemia could potentially be targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 118 publications
(202 reference statements)
1
33
0
Order By: Relevance
“…The observed reduction of the infarct volume was similar to that obtained in mice that were stereotactically injected into the cortex 3 weeks prior to MCAO with rAAVs containing expression cassettes for Npas4 (rAAV-Npas4) (Figures 2A-2D), which has potent neuroprotective activities. 2,5,21,22 It is also comparable to the reduction in stroke volume obtained using rAAV-mediated expression of Activin A. 8 This experiment also revealed that not every AID gene provides effective protection in the MCAO model of acute neurodegeneration.…”
Section: Neuroprotection After Intracerebroventricular Injection Of Rsupporting
confidence: 58%
“…The observed reduction of the infarct volume was similar to that obtained in mice that were stereotactically injected into the cortex 3 weeks prior to MCAO with rAAVs containing expression cassettes for Npas4 (rAAV-Npas4) (Figures 2A-2D), which has potent neuroprotective activities. 2,5,21,22 It is also comparable to the reduction in stroke volume obtained using rAAV-mediated expression of Activin A. 8 This experiment also revealed that not every AID gene provides effective protection in the MCAO model of acute neurodegeneration.…”
Section: Neuroprotection After Intracerebroventricular Injection Of Rsupporting
confidence: 58%
“…NPAS4 expression was lower in the cerebellar Purkinje cells of SCA1 mice than those of the WT mice, but this was reversed by treadmill training. Although the regulatory role of NPAS4 in SCA1 remains unclear, the protection of neurons against cerebellar ischemia and neurodegenerative insults in Huntington's disease through upregulated NPAS4 expression were demonstrated. Thus, we suggest that the exercise‐induced increase of cerebellar NPAS4 expression may have reflected the higher neuronal activity in the exercise‐trained SCA1 mice than the nontrained mice.…”
Section: Discussionmentioning
confidence: 99%
“…It participates in brain's responses to environmental aggression, shaping behavioral and stress responses [6]. Studies have revealed that Npas4 plays a role in stroke through modulation of apoptotic and inflammatory pathways [7]. Differential levels of Npas4 expression in the brain may regulate anxiety, depression and cognition related disorders [8].…”
Section: Introductionmentioning
confidence: 99%